Estudo de biomarcadores relacionados à agressividade e invasividade em carcinoma de células escamosas oral - Callegari, Eline Manhães Reid (2015)
In tumorigenesis process, laminin-332 performs multiple biologic effects by γ2 chain, and MMP-9 acts disrupting extracellular components. We aimed to assess the molecular profile of γ2 chain and MMP-9 in leukoplakias oral high-risk, carcinoma in situ (CIS) and oral invasive carcinoma cell squamous (OSCC) and establish possible associations with clinicopathologic features. γ2 chain and MMP-9 expression were assessed by immunohistochemistry in 10 patients with high-risk malignancy lesions and 26 cases of invasive OSCC. The immunostaining of γ2 chain in high-risk lesions showed most cases with a continuous basement membrane, on the other hand the majority of invasive OSCC had a discontinuous membrane or absence. OSCC stromal cells showed a higher presence of MMP-9 compared to cases of high-risk lesions. The association between clinical and expression profile demonstrated that smokers with invasive OSCC had a higher expression of γ2 chain in epithelium and MMP-9 in invasive fronts. A higher expression of MMP-9 in stromal cells was associated with male patients, older than 60 years and diagnosed with invasive OSCC when compared with high-risk lesions. Our results indicate an association between clinical and microscopic features in oral lesions with high malignant potential and oral carcinomas, with a progressive change in γ2 chain and MMP-9 expression during tumorigenesis.